Konsep Diri Polisi Wanita (Polwan) dalam Konteks Komunikasi Interpersonal di Polres Metro Bekasi - Kadek Alda Rahmawati; Maylanny Christin (COMMUNICATION MAJOR, 2021)
Abstract Working as policewomen is a challenging profession. As women, policewomen must be prepared to face a plethora of issues and conservative opposition from society, perform activities that are typically associated with men, have a feminine side in acting and protecting the community, and face domestic responsibilities. Policewomen are expected to have a strong self-concept in dealing with the risks of their job. This study aimed at understanding and determining the detailed description of policewomen self-concept in the context of interpersonal communication at the Bekasi Metro Police. This research employed a qualitative method with a phenomenological approach. The theory of self-concept and interpersonal communication was applied in this study. The four key informants were chosen using a purposive sample technique based on several criteria, including having served for at least four years and each representing one rank to ensure that there were differences in service experience. Observation, in-depth interviews, and documentation were used to collect data. After going through the data collection, data reduction, data display, and conclusion drawing processes, details of the policewoman's positive self-concept were discovered, which were characterized by five characteristics: being confident in their abilities, feeling equal to others, receiving praise without shame, understanding that everyone has different opinions, and having the ability for self-improvement. In interpersonal communication, a positive self-concept is required to strengthen the communication abilities of the informant both at work and in daily life, and it also plays critical role in enhancing informant's confidence to take the opportunity in honing their interpersonal skills. In addition, the researcher obtained fourteen symbolic meanings packaged from the experiences and pure thoughts of policewomen.Keywords: policewomen; self-concept; symbolic meaningAbstrak Bekerja menjadi seorang polisi wanita (polwan) bukanlah hal yang mudah. Sebagai wanita, polwan harus siap menghadapi berbagai macam tantangan konservatif masyarakat, mengemban tugas yang bermakna maskulin, memiliki sisi fenimin dalam bertindak dan mengayomi masyarakat dan memiliki beban domestik dalam keluarga. Polwan diharapkan memiliki konsep diri yang kuat dalam menghadapi resiko pekerjannya. Penelitian ini bertujuan untuk memahami dan mengetahui detail gambaran dari konsep diri polwan dalam konteks komunikasi interpersonal di Polres Metro Bekasi. Penelitian ini merupakan penelitian kualitatif yang dianalisis dengan pendekatan fenomenologis. Teori yang digunakan dalam penelitian ini adalah teori konsep diri dan komunikasi interpersonal. Keempat informan kunci dipilih menggunakan teknik purposive sampling dengan beberapa kriteria diantaranya yaitu minimal telah berdinas selama 4 tahun dan setiap informan mewakili satu pangkat yang ada sehingga terdapat perbedaan pengalaman selama berdinas. Pengumpulan data dilakukan dengan teknik observasi, wawancara mendalam dan dokumentasi. Setelah melalui proses data collection, data reduction, data display dan conclusion drawing, ditemukanlah detail konsep diri positif polwan yang ditandai dengan lima hal, yaitu yakin dengan kemampuan dirinya, merasa setara dengan orang lain, menerima pujian tanpa rasa malu, memahami bahwa setiap orang memiliki pendapat yang berbeda dan memiliki kemampuan untuk memperbaiki diri. Pada komunikasi interpersonal, konsep diri positif dibutuhkan untuk mengasah kemampuan komunikasi informan baik saat berdinas maupun dalam kehidupan sehari-hari dan mengambil peran penting dalam kepercayaan diri informan untuk mengambil peluang pengalaman mengasah kemampuan interpersonalnya agar lebih baik. Peneliti juga mendapatkan empat belas makna simbolis yang dikemas melalui pengalaman dan hasil pemikiran murni polwan.Kata Kunci: konsep diri; makna simbolis; polwan.